Sensing guanine and its derivatives: From molecular recognition to applications - Yuqing Li; Juewen Liu (Sensors and Actuators Reports, 2020)
Guanine plays an indispensable role in building nucleic acids, and its derivatives take part in various cellular functions such as regulating biological reactions and signal transduction. Monitoring the levels of guanine and its derivatives is critical for understanding their biological roles and related diseases. Aside from traditional chromatography-based methods, majority of the current detections were based on electrochemistry and the oxidation activity of guanine, for which guanine and adenine often had a similar response. Over the last 30 years, various new sensing strategies have been developed. To provide researchers with more options for specific sensing of guanine and its derivatives, herein we review molecular recognition strategies based on nucleic acids, proteins, small organic molecules, molecularly imprinted polymers to nanomaterials. The mechanism of each molecular recognition strategy is discussed. Based on these target recognition molecules, we also critically review representative fluorescent and electrochemical sensors for guanine-related analytes from an application point of view, and provide readers with our perspectives to further grow this direction.